KAJIAN PETANI KELAPA DALAM MENINGKATKAN KESEJAHTERAAN KELUARGA DI DESA PATOKAAN KECAMATAN TALAWAAN KABUPATEN MINAHASA UTARA - Andilan, Trendy Boy; Tumengkol, Selvie M.; Kandowangko, Nicolas (HOLISTIK, Journal Of Social and Culture, 2019)
Socio-economic Status is a condition or position that is socially regulated in a particular position in the community structure. The provision of this position is accompanied by a set of rights and obligations that are only fulfilled by the carrier of its status, so that land ownership is one of the factors that can determine the high or low socio-economic condition of a person in society.Agricultural land is a contributing factor to the life needs of the community, especially rural communities. Rural communities in general are people who use natural resources in the field of agriculture, where the community has hereditary activities in the agriculture sector, so that people in rural areas and The margins of earning or relying on businesses engaged in agriculture.Farmers are synonymous with marginalized people in the bustle of development. The unbiased situation on the farmer, then it affects the performance of farmers in their field. In North Minahasa regency, especially in the village of Patokaan Coconut is considered as one of the main livelihood for farmers to support the familyeconomy. Coconut plants are an efficient plant that is very beneficial to meet the needs of human day, because all parts of coconut tree can be used for human needs.By looking at the price of coconut in the market still fluctuating sometimes rises sometimes down but the farmers are still able to survive in cultivating coconut plants. The reason farmers are trying in coconut farming because coconut in its productivity in one year is able to get results as many as 4 (four) harvest.Keywords: agricultural, farmer, coconut